Species diversity and genetic variability of begomoviruses and associated DNA satellites infecting non-cultivated plants in Brazil and in Spain - Ferro, Camila Geovana (2016)
Begomoviruses (genus Begomovirus, family Geminiviridae) possess one or two genomic components of circular, single-stranded DNA (ssDNA) encapsidated in geminate icosahedral particles. Most begomoviruses in the New World (NW) are bipartite, while the majority in the Old World (OW) are monopartite and frequently associated with two classes of satellite DNAs: alphasatellites and betasatellites. Alphasatellites have been recently reported in association with bipartite begomoviruses in the NW. Members of the genus Begomovirus are responsible for important crop diseases worldwide. Begomoviruses that infect Ipomoea spp. (family Convolvulaceae), commonly known as "sweepoviruses", have the typical genomic organization of OW monopartite viruses but are phylogenetically distinct from all other species in the genus. Understanding the dynamics and genetic variability of viral populations in non-cultivated hosts is important for the prediction and consequent prevention of new virus diseases in cultivated plants. This work aimed to: (i) assess the diversity of begomoviruses in two non-cultivated hosts widely distributed in Brazil, Sida spp. and Leonurus sibiricus; (ii) determine the genetic structure and variability of begomovirus populations infecting Sida spp. and L. sibiricus; (iii) determine the genetic variability of deltasatellites associated with sweepoviruses infecting Ipomoea indica in Spain and expand the analysis to other geographical areas. For the first two objectives, total DNA was extracted from samples of Sida spp. and L. sibiricus collected in the states of Rio Grande do Sul, Paraná and Mato Grosso do Sul from 2009 to 2011 and viral genomes were amplified, cloned and sequenced. In Sida spp. the most prevalent virus was Sida micrantha mosaic virus (SiMMV). In addition, three new species were also detected. The vast majority of L. sibiricus samples were infected by Tomato yellow spot virus (ToYSV). Two alphasatellites were found: Euphorbia yellow mosaic alphasatellite in Sida sp. and a new alphasatellite associated with ToYSV in L. sibiricus. Both the SiMMV and ToYSV populations have a high degree of genetic variability. Although a high level of recombination was detected, mutational dynamics was the primary factor of diversification. The results were inconclusive regarding genetic structuration based on geography. For the third objective, DNA was extracted from I. indica samples collected in southern Spain in 2015 and rolling circle amplification (RCA), a technique that allows amplification of circular ssDNA molecules without previous knowledge of nucleotide sequence, was used to clone deltasatellites and two associated sweepoviruses, Sweet potato leaf curl virus (SPLCV) and Sweet potato mosaic virus (SPMV). Deltasatellites showed low sequence variability, no evidence of recombination, and no obvious geographical structuration. Also, a sweepovirus- deltasatellite chimera with a size similar to deltasatellites was detected.